Detection of effective parameters in arsenic removal with capacitive deionization process and arsenic removal from wastewater - Uzun, Halil; Debik, Eyüp (My University, 2019)
Access to water is a problem the magnitude of which increases day by day. In addition to water scarcity, water contamination also plays an important part in the exacerbation of this problem. Underground and surface waters can be polluted as a result of human activities as well as natural sources. One of the most commonly found natural pollutants is arsenic. Risks and effects of arsenic on health make it necessary to be treated from water. Conventional methods of arsenic removal make it necessary for new studies to be conducted because of problems such economical and special equipment needs. The MCDI process stands out with its advantages such as being economic, flexibly and installation a package process. In this study, using the optimum conditions which are operating times, flow rate, current, voltage, number of cycles, previously determined for Voltea brand MCDI, the removal of arsenic from the wastewater produced by Emet Bor Operation Directorate Espey Open Quarry and Concentrator Facility, Hisarcik Open Quarry and Concentrator Facility and Boric Acid Production Facility during their activities has been studied. The removal efficiency of the MCDI process for arsenic was 94%.